Effects of cooperative learning on English achievement, retention, and motivation among low-level students in a rural province of Thailand Pittaya Yamo - Pittaya Yamo,; Watcharee Wongthanate,; Pragasit Sitthitikul, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This mixed-method research aimed to examine how cooperative learning affected English achievement and motivation among low-level students in a rural province of Thailand. Using purposive sampling, the study focused on 30 seventh-grade students from an "opportunity expansion" school enrolled in English for Hospitality Industry, a university lifelong learning course, during the 2023 academic year. The research instruments included a learning activity package, achievement tests, semi-structured interviews, and a researcher’s log. Data were analysed using percentage, mean, standard deviation, t-test, and thematic analysis. Overall, the findings support the effectiveness of incorporating cooperative learning strategies into language education programmes aimed at enhancing students’ English proficiency and motivation. Achievement scores showed a significant increase immediately after the course, with a p-value of 0.00 (p < .05), and no statistically significant change two weeks after the course, with a p-value of 0.31 (p > .05), indicating skill retention. The positive impact of cooperative learning on English proficiency underscores its potential as a pedagogic approach to fostering lifelong learning among students. Educators and curriculum developers can benefit from integrating cooperative learning strategies into language education programmes, particularly in contexts like the hospitality industry, where effective communication skills are pivotal.